حرف الجر ( في ) وتناوبه مع غيره من حروف الجر - يونس يونس; حسين خديجة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Arabic language is distributed between a name, a verb and a letter; names form the greatest percentage of the language, followed by verbs then letters. Letters are divided between working and non-working, or a competent and incompetent, competent letters perform an impact on what followed, including the prepositions, and incompetent letters do not cause any little impact. Preposition (Fi) is one of prepositions, it has different semantic meanings, alternating with other prepositions in different places. But this research is about alternation of preposition (Fi) with others, it is mentioned in the introduction, next a definition of the letters, after that a talk about prepositions, then alternation of preposition (Fi) with other prepositions, as (a’la, min, ila, Alaba, m’a, nhwa, and ba’d), finally a conclusion contains the most important search results, and sources and references. تتوزع اللغة العربية ما بين اسم وفعل وحرف، وتشكل الأسماء النسبة الأكبر من اللغة ، تليها الأفعال فالحروف، وتُقسم الحروف ما بين عاملة وغير عاملة، أو مختصة وغير مختصة، والحروف المختصة تؤدي أثراً فيما يليها ومنها حروف الجر، أما الحروف غير المختصة فلا نجد لها أثراً يُذكر. وحرف الجر ( في ) واحد من حروف الجر، له معانٍ ودلالات مختلفة، ويتناوب مع غيره من حروف الجر في مواضع مختلفة ., ولهذا كان البحث حول تناوب حرف الجر ( في ) مع غيره ، فجاء في مقدمة ، ثم تعريف للحروف ، وبعد ذلك حديث عن حروف الجر ، ثم تناوب حرف ( في ) مع غيره من حروف الجر ، كـ ( على ، ومن ، وإلى ، والباء ، ومع ، ونحو ، وبعد ) ، ثم خاتمة جاء فيها أهم نتائج البحث ، ثم ثبت بالمصادر والمراجع .